HUBUNGAN JUMLAH GIGI DAN ASUPAN MAKANAN DENGAN STATUS GIZI (Kajian Pada Usia 50 Tahun ke Atas di Kalurahan Wirokerten dan Kalurahan Singosaren Kecamatan Banguntapan DIY) - , UTAMI A; , drg. Dibyo Pramono, SU, MD.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nutritional status is the picture of the balance of nutritional needs with food intake. Nutritional status is influenced by food intake, general health, oral health, socio-economics and environmental factors. Oral health factors that influence nutritional status is the number of teeth. Reduced number of teeth will reduced the ability of mastication of food. Difficulty in chewing resulted in changes in the amount and type of food intake. Changing consumption pattern will affect nutritional status. The purpose of this study was to determine the relationship between the number of teeth and food intake and nutritional status. This study is an observational study with cross-sectional design. In this study, the nutritional status was measured by calculating body mass index (BMI), calculated as kg/m2. The number of remaining teeth was calculated, the rest of the root tooth is considered as missing teeth and third molar are not counted. Food intake data was obtained by food recall method and calculated value of the individual AKG. The data were analyzed using simple regression analysis test with a significance level of 0.25 and a multiple regression analysis with a significance level of 0.05 level. Simple regression analysis results indicate that the variable number of teeth and food intake variables have a significance level of <0.25. Results of multiple regression analysis showed that the number of teeth has a significant relationship to the nutritional status of the 0.003 significance level and food intake had no significant relationship with the nutritional status significance level of 0.089. The conclusion from this study is that there is a relationship between the number of teeth with nutritional status and no relationship between dietary intake and nutritional status.